Optimization of Non-value Added Headcounts in Inventory Control: A Case Study in an Electronics Manufacturing Company (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Manufacturing companies are highly concerned with non-value added (NVA) activities that are unnecessary or wasteful from the customer’s perspective, and the employees who are responsible for these activities are considered as NVA headcounts. Consequently, this study aims to use the Define – Measure – Analyze – Improve – Control (DMAIC) process to solve this problem for an Electronics Manufacturing Company. It showed how to analyze the data and then defined that the Inventory Control process has the most NVA headcounts to start with the improvement, the SIPOC Model Diagram (SIPOC) was brought out to measure the target process. Useful methods like Cause and Effect Diagram (CED), 5 Whys, and Time Study Snapback (TSS) were used to analyze and indicate the root causes. In the improving stage, a new Inventory Control matrix was developed to reduce 13 NVA headcounts and save approximately 78000$ per year for the company. The study also listed out the activities that would have to do to maintain the project’s effectiveness.